Precise detection of CRISPR-Cas9 editing in hair cells in the treatment of autosomal dominant hearing loss - Chong Cui; Daqi Wang; Bowei Huang; Fang Wang; Yuxin Chen; Jun Lv; Luping Zhang; Lei Han; Dong Liu; Zheng-Yi Chen; Geng-Lin Li; Huawei Li; et al. (Elsevier, 2022)
Gene therapy would benefit from the effective editing of targeted cells with CRISPR-Cas9 tools. However, it is difficult to precisely assess the editing performance in vivo because the tissues contain many non-targeted cells, which is one of the major barriers to clinical translation. Here, in the Atoh1-GFP;Kcnq4+/G229D mice, recapitulating a novel mutation we identified in a hereditary hearing loss pedigree, the high-efficiency editing of CRISPR-Cas9 in hair cells (34.10% on average) was precisely detected by sorting out labeled cells compared with only 1.45% efficiency in the whole cochlear tissue. After injection of the developed AAV_SaCas9-KKH_sgRNA agents, the Kcnq4+/G229D mice showed significantly lower auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE) thresholds, shorter ABR wave I latencies, higher ABR wave I amplitudes, increased number of surviving outer hair cells (OHCs), and more hyperpolarized resting membrane potentials of OHCs. These findings provide an innovative approach to accurately assess the underestimated editing efficiency of CRISPR-Cas9 in vivo and offer a promising strategy for the treatment of KCNQ4-related deafness.